Extracellular Ubiquitin(1–76) and Ubiquitin(1–74) Regulate Cardiac Fibroblast Proliferation. Issue 4 (October 2018) - Jackson, Edwin K.; Mi, Eric; Ritov, Vladimir B.; Gillespie, Delbert G.
Abstract : SDF-1α (stromal cell–derived factor-1α) is a CXCR4-receptor agonist and DPP4 (dipeptidyl peptidase 4) substrate. SDF-1α, particularly when combined with sitagliptin to block the metabolism of SDF-1α by DPP4, stimulates proliferation of cardiac fibroblasts via the CXCR4 receptor; this effect is greater in cells from spontaneously hypertensive rats versus Wistar-Kyoto normotensive rats. Emerging evidence indicates that ubiquitin(1–76) exists in plasma and is a potent CXCR4-receptor agonist. Therefore, we hypothesized that ubiquitin(1–76), similar to SDF-1α, should increase proliferation of cardiac fibroblasts. Contrary to our working hypothesis, ubiquitin(1–76) did not stimulate cardiac fibroblast proliferation, yet unexpectedly antagonized the proproliferative effects of SDF-1α combined with sitagliptin. In this regard, ubiquitin(1–76) was more potent in spontaneously hypertensive versus Wistar-Kyoto cells. In the presence of 6bk (selective inhibitor of insulin-degrading enzyme [IDE]; an enzyme known to convert ubiquitin(1–76) to ubiquitin(1–74)), ubiquitin(1–76) no longer antagonized the proproliferative effects of SDF-1α/sitagliptin. Ubiquitin(1–74) also antagonized the proproliferative effects of SDF-1α/sitagliptin, and this effect of ubiquitin(1–74) was not blocked by 6bk and was >10-fold more potent compared with ubiquitin(1–76). Neither ubiquitin(1–76) nor ubiquitin(1–74) inhibited the proproliferative effects of the non-CXCR4 receptor agonist neuropeptide Y (activates Y1 receptors). Cardiac fibroblasts expressed IDE mRNA, protein, and activity and converted ubiquitin(1–76) to ubiquitin(1–74). Spontaneously hypertensive fibroblasts expressed greater IDE activity. Extracellular ubiquitin(1–76) blocks the proproliferative effects of SDF-1α/sitagliptin via its conversion by IDE to ubiquitin(1–74), a potent CXCR4 antagonist. Thus, IDE inhibitors, particularly when combined with DPP4 inhibitors or hypertension, could increase the risk of cardiac fibrosis. Abstract : Supplemental Digital Content is available in the text.